(3QSGdI Edi CHj SYjO Hf CHj GdNjQ GdUhas - (3GHi SYjO Hf GHi GdNjQ GdUhais; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3hHYO aGSGd ehdGi hQFjSj LOO Gddg Ydjg CfhGY GdSYGOI s
(3BNQgG (B:s
(3dTQhb fhQ Gddg ai GdSQ dGfcTGa GdZe GdeVdI ddfaS GdfGWbI s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B841s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3adSaI (B223) s
Keywords: (3GdadSaI hGdefWbs